Implikatur dalam Wacana tentang Covid-19 di Media Sosial - Tria Putri Mustika; Mangatur Sinaga (Balai Bahasa Provinsi Riau, 2022)
Since 2019, both national and international media have started to report all the problems massively related to the Covid -19 pandemic. This shall bring a positive impact if the information conveyed can be understood properly and correctly by recipients of the information, namely the Indonesian people in general. In this case, the concept of implicature is very important, especially if the information conveyed has an implied purpose. The purpose of this study is to describe 1) the type of implicature, and 2) the form and function of the implicature, in the discourse on covid-19 on social media. This research is descriptive-qualitative research using the content analysis method to reveal, understand, and catch the messages from the data, and deduce conclusions obtained through data identification and interpretation. The research findings revealed that the type of implicature found was a conventional implicature. While the implied types were declarative form used to invite and insinuate, imperative type used as satire, interrogative type used as satire too, and exclamative type used to express a command.